Innovative Work Behavior: A Review of Literature - Ahmad Al-Omari, Mohammad; Suan Choo, Ling; Asad Moh’d Ali, Mahmood (International Journal of Psychosocial Rehabilitation, 2019)
Innovation has been recognized as one of the main strategies for organizations to remain competitive in today’s competitive economy. Employees’ innovative work behavior is the primary driver for organizational-wide innovation. Innovative work behavior is the production of usable products, processes, or services originating from identifying problems to generating ideas. From the review of existing studies, this paper defines the concept of innovative work behavior, explaining why these behaviors are so important for organizations, and discusses the determinants of innovative work behavior.